Evolution of clinical trials in multiple sclerosis. (February 2019) - Zhang, Yinan; Salter, Amber; Wallström, Erik; Cutter, Gary; Stüve, Olaf
Clinical trials have advanced the treatment of multiple sclerosis (MS) by demonstrating the safety and efficacy of disease-modifying therapies (DMTs). This review discusses major changes to MS clinical trials in the era of DMTs. As treatment options for MS continue to increase, patients in modern MS trials present earlier and with milder disease compared with historic MS populations. While placebo-controlled trials for some questions may still be relevant, DMT trials in relapsing–remitting MS (RRMS) are no longer ethical. The replacement of the placebo arm by an active comparator arm in trials have raised the cost of trials by requiring larger sample sizes to detect on-study changes in treatment effects. Efforts to improve trial efficiency in RRMS have focused on exploring adaptive designs and relying on sensitive magnetic resonance imaging measures of disease activity. In trials for progressive forms of MS (PMS), the lack of sensitive outcome measures that can be used in shorter-term trials have delayed the development of effective treatments. Recent shifting of the focus to advancing trials in PMS has identified paraclinical outcome measurements with improved potential, and the testing of agents for neuroprotection and remyelination is in progress.